Easy to Read : Annie and Bo and the Big Surprise - Partridge, Elizabeth; Weston, Martha (New York : Dutton Children's Books, 2001)
Bo bakes a full moon cake as a surprise for his friend Annie, but the outcome is unexpected.
Keywords: Cake -- Fiction; Baking -- Fiction; Mice -- Fiction; Early chapter